1994
DOI: 10.2135/cropsci1994.0011183x003400020021x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance in Soybean of Resistant and Necrotic Reactions to Soybean Mosaic Virus Strains

Abstract: Five soybean [Glycine max (L.) Merr.] cultivars, PI96983, ‘Ogden’, ‘York’, ‘Marshall’, and ‘Kwanggyo’, were studied to determine the inheritance of their resistant (R) or necrotic (N) reactions to soybean mosaic virus (SMV) strains G4, G5, G6, G7, and G7A. Each parent was crossed reciprocally with a susceptible (S) cultivar (‘Essex’ or ‘Lee 68’) to determine the number of genes for resistance or necrosis. The R parents were also crossed with each other to test the allelism of the genes conditioning the R or N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 0 publications
5
71
2
Order By: Relevance
“…Perturbation of Avr or R genes (15,20,41), graft inoculation instead of mechanical inoculation (6,28,69,72), change in genetic background of the R gene-carrying plant (45), heterozygosity rather than homozygosity of the R-genotype plant (10,52,56), prevention of salicylic acid accumulation in the R-genotype plant (19,42), or temperature shift (30,70) can result in virus escape to distant tissues, provoking systemic HR (SHR) in resistant genotypes. Occasionally, SHR will result in the death of the infected plant, a condition termed lethal SHR (LSHR) (28,29).…”
mentioning
confidence: 99%
“…Perturbation of Avr or R genes (15,20,41), graft inoculation instead of mechanical inoculation (6,28,69,72), change in genetic background of the R gene-carrying plant (45), heterozygosity rather than homozygosity of the R-genotype plant (10,52,56), prevention of salicylic acid accumulation in the R-genotype plant (19,42), or temperature shift (30,70) can result in virus escape to distant tissues, provoking systemic HR (SHR) in resistant genotypes. Occasionally, SHR will result in the death of the infected plant, a condition termed lethal SHR (LSHR) (28,29).…”
mentioning
confidence: 99%
“…The spectrum of reactions includes resistance to systemic necrosis, lethal necrosis, and mosaic. Chen et al (1994) suggested that this range of complexities is controlled by the same gene. In Vigna unguiculata L., the Mvn-1 allele controls both the hypersensitive response to cowpea mosaic virus strain CPMV-LL and lethal necrosis to CPMV-TN (Patel 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The genes involved in the systemic necrosis response are genetically closely linked to resistance genes that condition the hypersensitive response. For instance, soybean cultivar PI 96983, which carries the gene Rsv1 (Kiihl and Hartwig 1979), has resistance to soybean mosaic virus (SMV) strains G1 to G6 (Chen et al 1994), but develops systemic necrosis when infected with strain G7 (Cho and Goodman 1979). In F 2 populations derived from crosses of PI 96983 with several cultivars that develop mosaic symptoms, the necrosis phenotype segregated 3 : 1 after inoculation with G7, suggesting that a single dominant gene, possibly Rsv1, controls necrosis (Chen et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was initially named Rsv and found in PI96983 soybean (Kiihl and Hartwig, 1979) and later renamed Rsv1 (Chen et al, 1991). Subsequent studies on soybean cultivars resistant to SMV revealed additional eight different Rsv1 alleles, from cultivars Ogden, York, Marshall, Kwanggyo, 'Raiden', 'Suweon 97', LR1 and PI507389, respectively (Kiihl and Hartwig, 1979;Buss et al, 1997;Buzzell and Tu, 1989;Chen et al, 1991Chen et al, , 1993Chen et al, , 1994Chen et al, , 2001Chen et al, , 2002Ma et al, 1995;Zheng et al, 2005). The responses of soybeans carrying these Rsv1 alleles to different SMV strains are diverse, ranging from extreme resistance and necrosis to mosaic symptoms.…”
Section: Smv-host Interactionsmentioning
confidence: 99%